Globalisation and South Asia: retrospect and prospect - International Seminar on Globalisation and South Asia: Retrospect and Prospect (1998 : University of Jayewardenepura); Indraratna, A. D. V. de S.; Sri Lanka Association for the Advancement of Science (Colombo : Sri Lanka Association for the Advancement of Science, 1999)
Contributed papers presented at the Seminar; held as part of the 54th Annual Sessions of Sri Lanka Association for the Advancement of Science.
Includes bibliographical references and index.
Mode of access: Internet.
2
Keywords: Globalization -- Economic aspects -- South Asia -- Congresses